2022
DOI: 10.2478/remav-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Housing Real Estate Prices on Inflation as One of the Most Important Factors: Poland’s Case

Abstract: The study aimed to examine the impact of inflation on the real estate market using Polish panel data for the last 13 years. It is based on a panel model, where price changes of one square meter of housing are determined as a function in changes of inflation, the central bank’s base rate, dwellings built, as well as new mortgage loans. The quarterly dynamics of the average price of 1 square meter of housing in Poland’s eight largest cities in the 2009-2021 period was studied. This price was modeled and predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Comparing the obtained results with other studies of the Polish market, we can recognize their correspondence with the results of Trojanek (2004) and Melnychenko et al (2022), indicating the inflationhedging ability of the Polish residential market. The discrepancy with the results of Wolski (2023), who concluded that the Polish residential market does not effectively hedge against inflation, is due to using different data and applying a different research method.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Comparing the obtained results with other studies of the Polish market, we can recognize their correspondence with the results of Trojanek (2004) and Melnychenko et al (2022), indicating the inflationhedging ability of the Polish residential market. The discrepancy with the results of Wolski (2023), who concluded that the Polish residential market does not effectively hedge against inflation, is due to using different data and applying a different research method.…”
Section: Discussionsupporting
confidence: 84%
“…Using three aggregated hedonic price indices of residential real estate (for 6, 7 and 10 of the biggest Polish cities), he stated that residential property prices and inflation rates (actual and expected) were not cointegrated, so Polish housing markets do not effectively hedge against inflation. For the same period, he also showed (2022), similarly to Melnychenko et al (2022), that the housing price index was positively correlated with inflation and concluded by raising the question of an appropriate method of assessing the hedging properties of assets.…”
Section: Realmentioning
confidence: 83%
See 1 more Smart Citation
“…In the Polish real estate market context, Melnychenko et al (2022) conducted a study on the impact of inflation on property prices in eight major cities from 2009 to 2021. The study covered Warsaw, Katowice, Lodz, Wroclaw, Gdansk, Bialystok, Krakow, and Poznan.…”
Section: Literature Review and Research Purposementioning
confidence: 99%
“…Surprisingly, Poznan showed little sensitivity to changes in inflation. Importantly, Melnychenko and colleagues accounted for other factors, such as the Polish Central Bank's base rate, the number of dwellings built, and new mortgage loans, in their model (Melnychenko et al, 2022). However, Wolski (2022) did not find evidence of a correlation between real estate prices and inflation in Poland during the same period, highlighting the need to explore real estate's potential as an inflation hedge in the country.…”
Section: Literature Review and Research Purposementioning
confidence: 99%